Cloning, Expression, and Enzymatic Characterization of Pseudomonas aeruginosa Topoisomerase IV - Akasaka, Takaaki (American Society for Microbiology, 1999)
The topoisomerase IV subunit A gene, parC homolog, has been cloned and sequenced from Pseudomonas aeruginosa PAO1, with cDNA encoding the N-terminal region of Escherichia coli parC used as a probe. The homolog and its upstream gene were presumed to be parC and parE through sequence homology with the parC and parE genes of other organisms. The deduced amino acid sequence of ParC and ParE showed 33 and 32% identity with that of the P. aeruginosa DNA gyrase subunits, GyrA and GyrB, respectively, and 69 and 75% identity with that of E. coli ParC and ParE, respectively. The putative ParC and ParE proteins were overexpressed and separately purified by use of a fusion system with a maltose-binding protein, and their enzymatic properties were examined. The reconstituted enzyme had ATP-dependent decatenation activity, which is the main catalytic activity of bacterial topoisomerase IV, and relaxing activities but had no supercoiling activity. So, the cloned genes were identified as P. aeruginosa topoisomerase IV genes. The inhibitory effects of quinolones on the activities of topoisomerase IV and DNA gyrase were compared. The 50% inhibitory concentrations of quinolones for the decatenation activity of topoisomerase IV were from five to eight times higher than those for the supercoiling activities of P. aeruginosa DNA gyrase. These results confirmed that topoisomerase IV is less sensitive to fluoroquinolones than is DNA gyrase and may be a secondary target of new quinolones in wild-type P. aeruginosa.